Similar topologies of individual‐based plant‐herbivorous networks in forest interior and anthropogenic edges. (28th January 2021) - Carvalho, Raquel L; Anjos, Diego V; Fagundes, Roberth; Luna, Pedro; Ribeiro, Sérvio Pontes
Abstract: Understanding the impacts of edge effects on ecological interactions plays an integral role in planning ecosystem recovery from human perturbations, as well as conservation of habitats. Edge effects related to forest fragmentation cause changes in species diversity that can disrupt ecological networks. Here, we evaluated how the diversity of, and interactions between, herbivorous insects associated with individuals of a pioneer plant species, Mabea fistulifera (Euphorbiaceae) are affected by the disturbances related to edge effects. We addressed two specific questions: (i) How do the forest edges affect species richness, abundance and composition of herbivorous interacting with M. fistulifera ? (ii) Do different disturbances related to edge effects affect the topology of individual‐based plant‐herbivorous networks? Herbivorous insects were sampled from three population patches of M. fistulifera in Brazilian Atlantic forest areas: two areas were subjected to distinct intensities of anthropogenic disturbances (firebreak and park access road, considered edges of low‐ and high‐impact, respectively), and one in the forest interior (control). We expected a lower species richness and abundance of herbivorous interacting with plants in forest edges than in the forest interior apart from to differences in the species composition. Therefore, based on these predictions, we expected that the various disturbances related to edge effects may change the topology of individual‐based plant‐herbivorous networks. We observed that species richness and abundance of herbivorous in high‐impact environments decreased in relation to forest interior, as well the species composition differed between these areas. Disturbance jeopardised network specialisation but did not change the topology of individual‐based networks, which presented a modular pattern. Edges affected herbivorous diversity and decreased the interaction overlap as individual‐based networks became highly specialised with increasing disturbance. These results enhance the understanding of edge effects and resilience of plant‐herbivorous interactions in regularly disturbed tropical environments. Abstract : Species richness and abundance of herbivorous in high‐impact environments decreased in relation to forest interior, as well the species composition differed between these areas. Disturbance jeopardised network specialisation but did not change the topology of individual‐based networks, which presented a modular pattern. Forest fragmentation and edges affect the diversity of herbivorous insects, but preserve the way these insects interact with pioneer tree species in the Brazilian Atlantic forest.